DIVERSITY AND ECOLOGY OF UNDERSTORY PLANT IN SEMPU ISLAND, EAST JAVA, INDONESIA - Hapsari, Lia; Abywijaya, Ilham Kurnia; Nurfadilah, Siti; Rindyastuti, Ridesti (SEAMEO BIOTROP, 2020)
As an indicator of environmental disturbances, the understory is an important structural and functional component of forest ecosystems. Hence, this study was conducted to assess the diversity and composition of understory plants in the lowland forests adjacent to the trekking paths along Semut Bay (dock entrance), Segara Anakan Lagoon, and several coastal areas in Sempu Island, and to determine their relationship with the underlying environmental factors as disturbance indicators through the presence of understory invasive alien species (IAS). Sixty site plots of 2 × 2 m² were established to analyze the understory vegetation, site profiles, and environmental variables. A total of 135 understory plant species belonging to 108 genera and 60 families were recorded within the 60 plots of the study areas. Poaceae was the dominant family, followed by Compositae, Phyllanthaceae, Sterculiaceae, Rubiaceae, Putranjivaceae, and Cyperaceae. The understory communities in the lowland forest adjacent to Semut Path were dominated by tree seedlings and had a relatively lower composition of shrubs. Coastal areas, which have more open canopies, were dominated by grasses and shrubs. Some dominant native understory species included Grewia spp., Cycas rumphii, and others. Indicating disturbance, 12 understory IAS were found in the study areas. Four of these are among the world’s worst invaders (Ageratum conyzoides, Chromolaena odorata, Lantana camara, Mikania micrantha), and three are noxious weeds (Eleusine indica and Imperata cylindrica). Light intensity and air temperature were strongly and positively associated with disturbed sites, while relative humidity, soil pH, and elevation were associated with less disturbed sites. The study results provide a scientific basis and recommendations on the current diversity status of understory plant species at Sempu Island, helping justify further conservation of indigenous species and their protection from disturbances.